678 Identification of asymmetries between longitudinal parameters and anthropometric proportionality ratios in children aged between 7 - 10 years (Balneo and PRM Research Journal, 2024)
The present study pursued the investigation of anthropometric asymmetries regarding the length of the upper and lower limbs and the indices of body proportionality and had the following ob-jectives: identifying the differences between the female and male groups, in the 4 age categories (7, 8, 9 and 10 years old), regarding anthropometric parameters and proportionality indicators; also tried to identify the differences in anthropometric parameters and proportionality indicators between the 4 age categories (7 - 10 years old) for each gender (female, respectively male). The study included 727 subjects with the age between 7-10 years, of which 383 (52.7%) female and 344 (47.3%) male, the subjects being divided into four groups according to age (7, 8, 9 and 10 years old groups). The measurements aimed at the following longitudinal anthropometric parameters and the calculation of proportionality ratios: height (cm); the length of the right upper limb (cm – LUL Right); the length of the left upper limb (cm – LUL Left); the length of the right lower limb (cm - LLL  Right); the length of the left lower limb (cm - LLL  Left); ratio of LUL Right X 100 / LLL Right; ratio of LUL Left x 100 / LLL  Left;  ratio of LUL Right x 100 / height; ratio of LUL Left x 100 / height;  ratio of LLL Right x 100 / height;  ratio of LLL_Left x 100/ height. Analyzing ccompara-tively the results recorded between the upper and lower right and left segments, we find asym-metry in all samples according to age and gender. The differences between the groups of girls and boys, in all age categories, were statistically significant. The ANOVA analysis reflects statis-tically significant differences between the 4 age groups (7 - 10 years) in all anthropometric evalu-ations. The largest asymmetries between the right and left upper limb were recorded in the age category of 7 years old group; respectively, the largest asymmetries between the lower limbs were recorded in the 10 year old groups depending on gender.